2016
DOI: 10.1039/c5ra25153b
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating binary anti-corrosion structures containing superhydrophobic surfaces and sturdy barrier layers for Al alloys

Abstract: The synergetic effect between the superhydrophobic surface and the barrier layer of anodic oxidation film make Al alloys show excellent anti-corrosion performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…Inspired with nature surface, such as lotus leaves, water strider legs, and cicada wings, 10,11 superhydrophobic surfaces are characterized by a static water contact angle (WCA) above 150 and a sliding angle (SA) less than 10 , by denition. 12,13 Due to the unique water-repellent property, superhydrophobic materials have gained tremendous interest, which has widespread applications in self-cleaning, 14,15 anti-icing, 16 metal anti-corrosion, 17 separation of oil and water, 18 especially in biomedical elds such as anti-sticking of protein, cells, and/or bacteria, [19][20][21] and drug release. 22,23 Therefore, the study of superhydrophobic gelatin materials is of great application value.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired with nature surface, such as lotus leaves, water strider legs, and cicada wings, 10,11 superhydrophobic surfaces are characterized by a static water contact angle (WCA) above 150 and a sliding angle (SA) less than 10 , by denition. 12,13 Due to the unique water-repellent property, superhydrophobic materials have gained tremendous interest, which has widespread applications in self-cleaning, 14,15 anti-icing, 16 metal anti-corrosion, 17 separation of oil and water, 18 especially in biomedical elds such as anti-sticking of protein, cells, and/or bacteria, [19][20][21] and drug release. 22,23 Therefore, the study of superhydrophobic gelatin materials is of great application value.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 There are previous reports describing the preparation of superhydrophobic surfaces. Wenjie Zhao et al 11 manipulated the etching pits and convex structure arranged regularly via chemical etching, anodic oxidation and self-assembly of PTES on Al alloys. The results showed that continuous and highly ordered nanopores formed a porous layer of anodic oxide lm, which was able to enhance the air trapping capability of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it revealed that the corrosion potential of superhydrophobic Co/a‐C:H film was −0.296 V, increased by 17.55% compared with the pure DLC film. The mechanism of corrosion resistance could probably be related to hydrophobicity of film . The change in corrosion performance might be similar to that of hydrophobicity.…”
Section: Resultsmentioning
confidence: 97%